AN ANALYSIS OF SENIOR HIGH SCHOOL STUDENTS’ MATHEMATICS COMPETENCY IN THE FREE TRADE ZONE OF RIAU ISLANDS PROVINCE, INDONESIA - Rahmatina, Desi; Bettiza, Martaleli (UPI Press, 2018)
This study is intended to provide an analysis of the competency map of senior high school students in the Final National Exam (FNE) for mathematics subject in Free Trade Zone (FTZ) of Riau Islands province. Sample was determined by examining secondary data in the form of 2014 Final National Examination (FNE) results published by the Education Assessment Center of the Ministry of Education and Culture of the Republic of Indonesia in the FTZ of Riau Islands Province, namely Batam, Bintan, and Karimun regencies. Criteria of sample determination were schools with lower Graduate Competency Standards (GCS) than the regency/city GCS, distribution of public or private schools, and distribution of school locations, with a total sample of 37 schools. The research was conducted by using descriptive statistical method to gain a description of the senior high school students’ competency in mathematics subject based on their FNE scores. The findings of this research can be made input and consideration for schools and government to improve the quality of education through analysis of the FNE results. The research results show that low GCS achievements were found in geometry and trigonometry topics, especially in the skills of determining position, distance, and magnitude of angles involving points, lines, and fields in solid geometry. The mean percentage of GCS mastery in the FTZ was 22.86%, with Batam 26.02%, Bintan 18.66%, and Karimun 18.72%. The result of the interview shows that the low GCS is caused by the lack of teaching media in the visual forms or simulators to build students’ understanding and limited time allocated in teaching. The solution recommended to solve this problem is by applying ICT-based learning to improve students’ understanding of geometry and trigonometry materials and also the use of video conferencing during mathematics teacher working group meetings.